220k views
11 votes
What is the answer ???????????????

What is the answer ???????????????-example-1
User Tdaff
by
5.2k points

2 Answers

3 votes

Answer:

(2, - 1 )

Explanation:

Given the 2 equations

y = 4x - 9 → (1)

y = x - 3 → (2)

Substitute y = 4x - 9 into (2)

4x - 9 = x - 3 ( subtract x from both sides )

3x - 9 = - 3 ( add 9 to both sides )

3x = 6 ( divide both sides by 3 )

x = 2

Substitute x = 2 into either of the 2 equations for y

Substituting into (2)

y = 2 - 3 = - 1

solution is (2, - 1 )

User Ako
by
5.4k points
6 votes
4(-3)-9 =-21. I hope this helpsss
User Federico Galfione
by
5.0k points